A Portable Fluorescence Camera for Testing Surgical Specimens in the Operating Room: Description and Early Evaluation - Kakareka, John W.; McCann, Thomas E.; Kosaka, Nobuyuki; Mitsunaga, Makoto; Morgan, Nicole Y.; Pohida, Thomas J.; Choyke, Peter L.; Kobayashi, Hisataka (Molecular imaging and biology, 2011)
Purpose Clinical translation of novel optical probes requires testing of human specimens ex vivo to ensure efficacy. However, it may be difficult to remove human tissue from the operating room due to regulatory/privacy issues. Therefore, we designed a portable fluorescence camera to test targeted optical imaging probes on human specimens in the operating room. Procedures A compact benchtop fluorescence camera was designed and built in-house. A mouse xenograft model of ovarian cancer with an activatable imaging probe based on rhodamine green was used to test the device. Comparison was made to commercially available imaging systems. Results The prototype camera produced images comparable to images acquired with commercially available, non-portable imaging systems. Conclusion We demonstrate the feasibility of a specimen-based portable fluorescence camera for use in the operating room. Its small size ensures that tissue excised from patients can be tested promptly for fluorescence within the operating room environment, thus expediting the testing of novel imaging probes.